Tecnologias e mídias digitais no processo educativo e a autoria de alunos: limites, contribuições e possibilidades - Menezes, Maria Eduarda de Lima (2013)
This study focuses on researching the possibilities and limits of student authorship promoted through the use of digital Communication and Information Technologies (CIT) and of digital media. The investigation also analyzes the role of these tools in contributing for the development of student authorship in the educational process at one selected school. The purpose of this study resides in the relevance of the theme today since communication, production, use and sharing of information are increasingly more present in social and virtual relationships. Furthermore, there are few studies about the topic, and even fewer which analyze student authorship through the use of digital media and CIT. The context of study is a private school in the city of Sao Paulo, which has been developing practices with digital CIT for over 10 years. One of such practices is the workshop about production of multimedia news content, which is offered from 7th graders to the senior year of high school. This is a qualitative study that used focus group protocol involving eight students and the teaching team, which included the teacher, the school principal and two journalists, besides the application of a questionnaire with the students and a documental analysis based on the workshop planning and the students blog. Results showed that students exert their authorship with responsibility and awareness, with the help of teachers mediation. During the process of creation and content production, students exert their authorship both individually and collectively, which allows for collaboration and interaction among them. They frequently resort to digital media and CIT to express their ideas through a number of different languages, and for the creation of news stories - which requires the development of creativity, autonomy and a critical view from their participants. Hence, students are no longer consumers: they start to be the producers of information which is shared in the knowledge network of the digital culture. It also shows that exercising authorship is the type of practice that contributes to build knowledge with the students in an active and engaged manner and presents viewpoints that enhance the integration of digital media and CIT in the educational process